Study on Granite Permeability Zoning Based on Electrical Resistivity: Take Wuyue Pumped Storage Power Station as an Example. (5th October 2022) - Huang, Zhiquan; Ran, Tao; Dong, Jinyu; Yuan, Guangxiang; Zhao, Guizhang
Abstract : A granite mass in Xinyang, China, was studied to better understand the features of the link between permeability and resistivity. The permeability coefficient of subsurface media has a certain correlation with electrical conductivity. The following steps are conducted in this method; first, water pressure tests were conducted on the borehole to determine the permeability of the granite mass at different depths; next, the electrical resistivity values of the borehole rock were determined using geophysical logging techniques; finally, three mathematical models were chosen to construct the relationship between the two, and their applicability in the study area was confirmed. The method has some applicability and can serve as a guide for the design of reservoir impermeability. It was discovered that the calibration permeability obtained by inverting the power function model has the greatest applicability and can be applied to the permeability zoning of two high-density logging lines to obtain the characteristic dividing line of 0.5 Lu and 1.0 Lu more clearly and that this method has certain applicability and can serve as a reference for the design of reservoir impermeability.